The Narrative Approach: Leveraging Storytelling Techniques for Enhanced English Fluency - Najm Burhan; Nia'am Hasan (مجلة ابحاث ميسان)
This Paper examines the role of history in Tanushree Podder’s Escape from Harem. It attempts to explore the history in the novel as a manifestation of the consecutive exemplification of the contemporary dynasty and how it affects the current social and political status quo. As such, the significance of the representations of history corresponds to the fact that ethnicity would be understood in the light of historical elements as being depicted by Podder. This is due to the fact that the perception of ethnicity, moreover, results in comprehension of its nations, traditions, norms, culture, and customs and the like. Consequently, the representations of history is an implicative representations of history of Mughal community, which is the core indication of history portrayed in the novel. As such, the aim of this study is to explore the intricate layers of history through its influence upon the Indian society and how they intersect with each other throughout historical periods. Thus, the study’s methodology will be limited to the concept of tradition and its relationship with culture and society.